Salience-based Contextualism in the Explanation of Communicative Success - Chávez Carvajal, Pablo David (Analysis. Journal of Philosophical Research, 2024)
This article analyzes how people interpret the meaning of utterances used in conversations, particularly when the meaning of words changes depending on the context. It focuses on a version of a theory called prominence-based contextualism, which explains how speakers understand the meanings of key expressions used in conversation. The article argues that the ability of interlocutors to comprehend what a speaker meant at a specific moment (communicative success) depends on their understanding of the most prominent meaning of the words used. This understanding is determined by the situation in which the words were spoken, and it does not require knowing the speaker’s communicative intention. The theory of salience contextualism proposes a word meaning formulation based on five sources of information: beliefs about the world, the meaning of words and sentence structure, the speech situation, the properties of the human inferential system, and stereotypes and presuppositions about society and culture.